Water management and its role in sustainable agricultural development in Anbar Governorate - Al.Duleimi, Amna J. (Al-Adab Journal, 2015)
Iraq have climate condition dry and sub dray , moreover evergehigh Evaporation and quantity limited , Euphrates river come from out Borders more over null Artevies feed it inside the Provence from these water resources of renewal are Basic of Economical and social development for country or Provence , there for study aim to disclose role of water management in sustainable of Agricultural , during arrangement of inrestment and good using for water resources of available in availability and whole need to it multisctorsas agricultural , in dustrial or houses during follow water management contribute in process of agricultural sustainable development in Governorate